The pleasure of working with Jacques Wallet - (:unkn) unknown (My University, 2021)
Jean-Pierre Chevalier got to know Jacques Wallet when they were both teaching Geography in normal schools in the Île-de-France region. Both were driven by a desire to transmit and disseminate knowledge, to use audiovisual media to do so. Their paths crossed. This portrait relates to Jacques as a didactician of geography, a film director, a pioneer of online distance education and especially in Africa.
Keywords: African Research